2016
DOI: 10.1002/cncr.30365
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and risk of esophageal adenocarcinoma in elderly patients in the United States: An analysis of SEER‐Medicare data

Abstract: Background Metabolic syndrome (MetS) is associated with cancer risk and increases the risk of Barrett’s esophagus, the precursor lesion of esophageal adenocarcinoma (EA), primarily in the absence of gastroesophageal reflux disease (GERD). However, little is known about whether MetS is associated with risk of EA. Methods Using the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database we evaluated whether MetS was associated with EA. EA cases (n=3,167) were compared with individually matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
0
41
0
1
Order By: Relevance
“…22 The other studies included were either esophageal squamous cell carcinoma, the other primary type of esophageal cancer which has a different etiology, 67 or a mixture of histological subtypes. Several previous studies have suggested that diabetes increases the risk of EA, [23][24][25][26][27][28] whereas others showed…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…22 The other studies included were either esophageal squamous cell carcinoma, the other primary type of esophageal cancer which has a different etiology, 67 or a mixture of histological subtypes. Several previous studies have suggested that diabetes increases the risk of EA, [23][24][25][26][27][28] whereas others showed…”
Section: Discussionmentioning
confidence: 93%
“…The other studies included were either esophageal squamous cell carcinoma, the other primary type of esophageal cancer which has a different etiology, or a mixture of histological subtypes. Several previous studies have suggested that diabetes increases the risk of EA, whereas others showed no association . Of the 3 prior studies showing no association between diabetes and EA, 1 is included in the current pooled analysis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations